Ocular vestibular evoked myogenic potentials elicited with vibration applied to the teeth. Issue 1 (January 2016) - Parker-George, Jennifer C.; Bell, Steven L.; Griffin, Michael J.
Highlights: This study investigates if applying stimulation directly to the teeth improves measurement of the vibration-induced oVEMP. Applying 100-Hz vibration tone pips directly to the teeth via a customised bite-bar elicits clearer oVEMP responses than direct application to the head. The quality and amplitude of vibration-induced oVEMPs is dependent on stimulus characteristics. Abstract: Objectives: This study investigated whether the method for eliciting vibration-induced oVEMPs could be improved by applying vibration directly to the teeth, and how vibration-induced oVEMP responses depend on the duration of the applied vibration. Methods: In 10 participants, a hand-held shaker was used to present 100-Hz vibration tone pips to the teeth via a customised bite-bar or to other parts of the head. oVEMP potentials were recorded in response to vibration in three orthogonal directions and five stimulus durations (10–180 ms). The oVEMP responses were analysed in terms of the peak latency onset, peak-to-peak amplitude, and the quality of the trace. Results: Vibration applied to the teeth via the bite-bar produced oVEMPs that were more consistent, of higher quality and of greater amplitude than those evoked by vibration applied to the head. Longer duration stimuli produced longer duration oVEMP responses. One cycle duration stimuli produced responses that were smaller in amplitude and lower quality than the longer stimulus durations. Conclusions: Application of vibration via the teeth using a bite-bar is an effective means of producing oVEMPs. A 1-cycle stimulus is not optimal to evoke an oVEMP because it produces less robust responses than those of longer stimulus duration. A positive relationship between the duration of the stimulus and the response is consistent with the notion that the vibration-induced oVEMP is an oscillatory response to the motion of the head, rather than being a simple reflex response that occurs when the stimulus exceeds a threshold level of stimulation. Significance: Applying acceleration to the teeth through a bite-bar elicits clearer oVEMP responses than direct application to other parts of the head and has potential to improve clinical measurements. A 100-Hz 1-cycle stimulus produces less robust oVEMP responses than longer 100-Hz stimuli.